Beta-alanine supplementation improves throwing velocities in repeated sprint ability and 200-m swimming performance in young water polo players - Claus, Gabriel Machado [UNESP]; Redkva, Paulo Eduardo [UNESP]; Brisola, Gabriel Mota Pinheiro [UNESP]; Malta, Elvis Sousa [UNESP]; De Araujo Bonetti De Poli, Rodrigo [UNESP]; Miyagi, Willian Eiji [UNESP]; Zagatto, Alessandro Moura [UNESP] (Human Kinetics, 2017)
The purpose of this study was to investigate the effects of beta-alanine supplementation on specific tests for water polo. Fifteen young water polo players (16 ± 2 years) underwent a 200-m swimming performance, repeated-sprint ability test (RSA) with free throw (shooting), and 30-s maximal tethered eggbeater kicks. Participants were randomly allocated into two groups (placebo × beta-alanine) and supplemented with 6.4g·day-1 of beta-alanine or a placebo for six weeks. The mean and total RSA times, the magnitude based inference analysis showed a likely beneficial effect for beta-alanine supplementation (both). The ball velocity measured in the throwing performance after each sprint in the RSA presented a very like beneficial inference in the beta-alanine group for mean (96.4%) and percentage decrement of ball velocity (92.5%, likely beneficial). Furthermore, the percentage change for mean ball velocity was different between groups (beta-alanine=+2.5% and placebo=-3.5%; p = .034). In the 30-s maximal tethered eggbeater kicks the placebo group presented decreased peak force, mean force, and fatigue index, while the beta-alanine group maintained performance in mean force (44.1%, possibly beneficial), only presenting decreases in peak force. The 200-m swimming performance showed a possibly beneficial effect (68.7%). Six weeks of beta-alanine supplementation was effective for improving ball velocity shooting in the RSA, maintaining performance in the 30-s test, and providing possibly beneficial effects in the 200-m swimming performance.
Keywords: Carnosine; Ergogenic aid; Specific tests; Team sports